Fungal Diversity in Himalayas : a Case Study for Conservation - Bisht, N. S.; Singh, Y. P.; Harsh, N. S. K. (Indian Forester, 1999)
To study the mycological wealth of Kumaun Himalayas, extensive surveys were conducted. The common edible, poisonous, ectomycorrhizal, fungicolous, rare, wood-decaying fungi and their commercial uses are discussed. In-situ and Ex-situ conservation of fungi for fungal diversity has also been suggested.